Pengembangan e-Module Kejuruan dengan Memanfaatkan Website Intranet untuk Meningkatkan Kompetensi Keahlian Teknik Elektronika Industri di SMKIT Darussalam 01 Batam - Tri Wawan Sugiarto; Zulfitria Zulfitria (Lembaga Yasin AlSys, 2026)
Although vocational learning in the Industrial Electronics Engineering competency has been widely examined, the use of structured and contextual digital learning media that do not rely on external internet access remains limited, particularly in the form of intranet website–based e-modules in vocational high schools. This study aimed to develop an intranet website–based vocational e-module and to analyze its feasibility and effectiveness in improving Industrial Electronics Engineering competencies at SMKIT Darussalam 01 Batam. The study employed a Research and Development approach using the ADDIE model and combined qualitative and quantitative methods. The participants consisted of 32 Grade X students selected through purposive sampling. Data were collected through observations, interviews, validation questionnaires administered to media and content experts, as well as pretest and posttest assessments, and were analyzed using descriptive statistics and qualitative descriptive analysis. The findings indicated that the developed e-module fell within the valid to very valid categories based on expert evaluations and was effective in enhancing students’ competencies, as reflected in the increase in the mean score from 64.37 in the pretest to 84.37 in the posttest. These results provide practical contributions to the development of intranet-based vocational learning media and broaden the application of multimedia learning theory in practical learning contexts. The study underscores the importance of intranet website–based e-modules as an effective alternative form of digital learning and recommends further development across various competency areas and more diverse school contexts.